Keputusan Pembelian Berdasarkan Desain Dan Kustomisasi Pada Produk Masker (Studi Pada Generasi Milenial Di Masa Pandemik) - Hilmi, Luqman Dzul (FEB Universitas Sultan Ageng Tirtayasa, 2021)
Must to use masks during this pandemic directly benefits the mask business in the form of increased mask sales. This condition requires business people to offer masks in addition to functioning as personal protective equipment, they also consider product design and product custom. The goal is to strengthen customers in the decision to buy masks that in addition to their needs, also their interests. In addition, advances in internet technology have made its use increasing. The increase is from the aspect of usage intensity to the level of browsing to internet-based media. The existence of the internet actually makes customers, especially the millennial generation, have more and more information in making purchase decisions, namely for mask products. Therefore, in this study using a quantitative approach with multiple regression analysis. Sampling of 129 millennial generation respondents used the accidental sampling method, namely accidental sampling of prospective respondents met, so that consideration of the suitability of the requirements must be fulfilled. Based on the results of data analysis, it was found that: 1) product design has a positive and significant effect on purchasing decisions; 2) product custom has a positive and significant effect on purchasing decisions; and 3) product design and custom have a positive and significant effect on purchasing decisions.